The Effect of Ease of Use of the "HADIRR" Application, Work Discipline, and Attendance Compliance on Employee Performance at PT. Hatten Bali Tbk. Sanur Denpasar Bali - I Dewa Gde Dharma Kinandana; Ni Komang Prasiani; I Made Satrya Ramayu (JURNAL ECONOMINA, 2026)
This study aims to analyze the effect of ease of use of the "HADIRR" application, work discipline, and attendance compliance on employee performance at PT Hatten Bali Tbk and uses a quantitative method with a causal associative approach. The data collection instrument is a questionnaire with five assessment scales (Likert scale) and distributed to 92 respondents. Furthermore, the data analysis tool uses SPSS ver 25. The results of this study indicate that partially (t-test) work discipline and attendance compliance have a significant influence on employee performance, then for ease of use of the "HADIRR" application has no influence on employee performance. Second, the simultaneous test of this study that all three variables have a significant influence simultaneously on employee performance at PT Hatten Bali Tbk. The coefficient of determination shows that changes in Employee Performance are influenced by Ease of Use of the Application, Work Discipline, and Attendance Compliance by 50.7%. This study concludes that the ease of use of the "HADIRR" application should be carried out more promptly (scheduled evaluation) in conducting daily attendance.